Effects of the eurozone crisis on the spanish healthcare system and economic sectors - Mehrad, Aida; Mehrad, Anita; Tahriri Zangeneh, Mohammad Hossein (Open Science Journal, 2024)
The current research focused on the effects of the eurozone crisis on the Spanish healthcare and economy sectors, what caused the crisis, and how Europe managed this crisis, especial. The importance of the eurozone crisis is apparent in businesses and economics segments; in fact, it has directed a defeat of confidence in European companies and economies. The crisis was ultimately maintained by the financial guarantees of European countries, who feared the euro's collapse and financial contagion, and by the International Monetary Fund (IMF). By knowing these essential points, the present study aimed to evaluate and find the primary and critical point about the crisis and the role of healthcare that is vital and significant nowadays and will help make a better healthcare system and offer services to high-quality individuals in Spain. Therefore, the researcher focused on different studies, such as articles, books, websites, etc., that are related to this area and based on this research, obtained 44 related and curated references that help conduct this paper and will be beneficial for future investigations in this area.